2011
DOI: 10.1136/bcr.09.2011.4860
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral polymicrogyria: always think in chromosome 22q11.2 deletion syndromes

Abstract: Polymicrogyria (PMG) is a malformation of cortical development due to an abnormal organisation. It is a heterogeneous disorder associated with genetic and acquired events, namely 22q11.2 deletion syndrome also known as DiGeorge syndrome (DGS) /velocardiofacial syndrome (VCFS) among others. This association has been known since 1996 and more than 30 cases have been described. Neurological features include motor and cognitive impairment, epilepsy, microcephaly and spasticity. The authors present an 8-month old i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“… 4 6 7 Among the detected structural abnormalities, malformations of cortical development including polymicrogyria, focal cortical dysplasia, and subependymal heterotopia appeared relatively frequently in the current patient series, as found in previous studies. 13 14 There are several recent reports of microdysgenesis of the brain in genetic generalized epilepsy or juvenile myoclonic epilepsy. 25 26 As indicated above, epilepsy that arises in 22q11.2DS is closely associated with genetic generalized epilepsy, suggesting the presence of microscopic morphological changes in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 6 7 Among the detected structural abnormalities, malformations of cortical development including polymicrogyria, focal cortical dysplasia, and subependymal heterotopia appeared relatively frequently in the current patient series, as found in previous studies. 13 14 There are several recent reports of microdysgenesis of the brain in genetic generalized epilepsy or juvenile myoclonic epilepsy. 25 26 As indicated above, epilepsy that arises in 22q11.2DS is closely associated with genetic generalized epilepsy, suggesting the presence of microscopic morphological changes in the brain.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Furthermore, the present study also demonstrated other rare congenital brain anomalies related to the syndrome such as an anomaly of the cerebral vasculature like hypoplasia of the intracranial artery 21 and a Chiari malformation. 28 Various imaging and histopathological findings in 22q11.2DS have been attributed to a direct effect of the chromosomal microdeletion, 14 21 22 23 and active surveillance for brain malformations can help patients with 22q11.2DS and NP manifestations. The disrupted expression of multiple genes involved in the development and maturation of neurons, neurotransmission, and neuronal circuits 4 5 can explain the broad spectrum of structural abnormalities, epilepsy, and the coexistence of several NP manifestations in 22q11.2DS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MRI indicated cortical malformation in the right hemisphere of our patient, interictal FDG-PET revealed bilateral hypometabolism. This possibly indicated bilateral PMG, which is indicative of brain malformation in patients with 22q11.2DS (Castro et al, 2011).…”
Section: Average Fits/days Daymentioning
confidence: 93%